Social administration : development and change : essays in honour of Professor V. Jagannadham - Jagannadham, Vedula; Chaturvedi, Triloki Nath; Chandra, Shanta Kohli (Indian Institute of Public Administration, 1980)
Festschrift honoring Vedula Jagannadham, b. 1918, professor of social administration and a former director of the Indian Institute of Public Administration, New Delhi.